2007
DOI: 10.1029/2006gl028848
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic coupling of volcanic CO2 flow and wind at the Horseshoe Lake tree kill, Mammoth Mountain, California

Abstract: [1] We investigate spatio-temporal relationships between soil CO 2 flux (F CO2 ), meteorological variables, and topography over a ten-day period (09/12/2006 to 09/21/ 2006) at the Horseshoe Lake tree kill, Mammoth Mountain, CA. Total CO 2 discharge varied from 16 to 52 t d À1 , suggesting a decline in CO 2 emissions over decadal timescales. We observed systematic changes in F CO2 in space and time in association with a weather front with relatively high wind speeds from the west and low atmospheric pressures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
57
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 22 publications
6
57
0
Order By: Relevance
“…Studies have reported large diurnal to seasonal fluctuations in time series of soil CO 2 concentrations, surface CO 2 fluxes, and total CO 2 discharges that appear to be due to variations in meteorological and hydrologic processes (e.g., McGee and Gerlach, 1998;McGee et al, 2000;Rogie et al, 2001). Also, Lewicki et al (2007) showed that large spatiotemporal variations in surface CO 2 fluxes over multiple days can be driven by slow-moving cold fronts. Furthermore, longterm monitoring suggests that emissions have markedly declined over the past decade.…”
Section: Study Sitementioning
confidence: 99%
See 3 more Smart Citations
“…Studies have reported large diurnal to seasonal fluctuations in time series of soil CO 2 concentrations, surface CO 2 fluxes, and total CO 2 discharges that appear to be due to variations in meteorological and hydrologic processes (e.g., McGee and Gerlach, 1998;McGee et al, 2000;Rogie et al, 2001). Also, Lewicki et al (2007) showed that large spatiotemporal variations in surface CO 2 fluxes over multiple days can be driven by slow-moving cold fronts. Furthermore, longterm monitoring suggests that emissions have markedly declined over the past decade.…”
Section: Study Sitementioning
confidence: 99%
“…Furthermore, longterm monitoring suggests that emissions have markedly declined over the past decade. For example, the average estimated CO 2 discharge from the tree kill area was~250 t d − 1 for 1995 to 1997 and 93 t d − 1 for 1997 to 2000 , whereas the average discharge measured in 2006 was 38 t d − 1 (Lewicki et al, 2007).…”
Section: Study Sitementioning
confidence: 99%
See 2 more Smart Citations
“…Laser rangefinders have been used previously in diverse research applications such as structural bedrock mapping of the Sheep Mountain anticline (Allwardt et al, 2007), mapping of ground fissures involved in coal bed fires (Ide et al, 2010) and recording positions of rutting elk and their behaviour with regards to vehicle traffic (St. Clair and Forrest, 2009). A laser rangefinder has also been used to create small scale digital terrain models by interpolating point measurements (Lewicki et al, 2007). To our knowledge, use of a laser rangefinder for determining distributed snow depth is a unique application of this technique.…”
Section: Introductionmentioning
confidence: 99%